How Much Labor Do South African Exports Contain? - Cali, Massimiliano; Hollweg, Claire H. (World Bank, Washington, DC, 2017)
Like many emerging economies, South Africa has identified exports as an engine for more inclusive, job-intensive growth. However, employment growth did not follow the substantial export growth that South Africa experienced in the 2000s. This paper uses a newly developed World Bank database -- the Labor Content of Exports -- to show that the composition of South Africa's export growth helps to understand the weak relationship between export and employment growth. Minerals exports, which propelled export as well as wage growth, are not job intensive and as a result supported far less job growth. Minerals have also increasingly become an enclave sector with few backward linkages to the domestic economy. In contrast, manufacturing exports support jobs and wages primarily in input-providing sectors, where indirect manufacturing employment is nearly 4.5 times greater than direct manufacturing employment. The paper also documents a shift in the labor content of global value chain–intensive manufacturing sectors away from direct manufacturing to indirect services. Such a shift has been biased toward skilled labor. As a results of these trends, labor in services sectors has been the main beneficiary of South Africa's export growth, absorbing more than half of the growth in wage income from exports over the 2000s, primarily by supplying inputs to other sectors' exports.